DZIELIMY SIĘ DOŚWIADCZENIEMAn enlargement of the right ventricle – what lies behind it? - Piechowiak, Monika; Maciejewski, Marek; Piestrzeniewicz, Katarzyna; Bartczak, Karol; Jaszewski, Ryszard; Drożdż, Jarosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Systolic-diastolic dysfunction of the right ventricle (RV) can be observed in the left ventricular myocardial (LV) associated with necrosis of RV muscle, pulmonary embolism, atrial septal defect or ventricular septal defect (VSD). Ischaemia or myocardial necrosis of the RV are usually underlying the dysfunction. Above-mentined conditions are very important in the haemodynamics of the RV, and ultimately the entire heart. Pulmonary embolism initially leads to rapid dilatation of the RV, followed by the rapid development of pulmonary hyperten-sion (PH). In the era of the treatment of coronary angioplasty, the incidence of VSD has been reduced considerably and is around 0.2%. Peri-infarction VSD in about 2/3 of cases relates to attacks involving the anterior wall, but the greater risk of death is associated with infarcts in the inferior wall. A new VSD usually goes with the cardiogenic shock or pulmonary edema, which significantly increase, both, hospital and perioperative mortality. In the diagnosis of peri-infarction VSD by transthoracic echocardiography is often sufficient, in which in addition to assessing the size and shape of the defect, the contractile function of both ventricles with the volume of mitral regurgitation can be assessed. The degree of the diastolic dysfunction RV significantly influences the reduction of the PH. Proceeding of choice in the peri-infarction VSD is cardiac surgery which involves setting patches on the septal defect and adjacent necrosis tissue. In the case of contraindications to the surgery, the proceeding of choice is to close the defect by a percutaneous intervention.